A Novel Mutation in RPL10 (Ribosomal Protein L10) Causes X‐Linked Intellectual Disability, Cerebellar Hypoplasia, and Spondylo‐Epiphyseal Dysplasia. Issue 12 (14th September 2015) - Zanni, Ginevra; Kalscheuer, Vera M.; Friedrich, Andreas; Barresi, Sabina; Alfieri, Paolo; Di Capua, Matteo; Haas, Stefan A.; Piccini, Giorgia; Karl, Thomas; Klauck, Sabine M.; Bellacchio, Emanuele; Emma, Francesco; et al.
Abstract : RPL10 encodes ribosomal protein L10, a highly conserved multifunctional component of the large ribosomal subunit, involved in ribosome biogenesis and function. Mutations in RPL10 cause autism or X‐linked intellectual disability associated with microcephaly, ataxia and absence of autistic features. This study expands the set of pathological mutations in RPL10, identifies a new form of X‐linked Spondylo‐epiphyseal dysplasia (SED) and highlights the emerging role of ribosomal proteins in skeletal and neurodevelopmental disorders. ABSTRACT: RPL10 encodes ribosomal protein L10 (uL16), a highly conserved multifunctional component of the large ribosomal subunit, involved in ribosome biogenesis and function. Using X‐exome resequencing, we identified a novel missense mutation (c.191C>T; p.(A64V)) in the N‐terminal domain of the protein, in a family with two affected cousins presenting with X‐linked intellectual disability, cerebellar hypoplasia, and spondylo‐epiphyseal dysplasia (SED). We assessed the impact of the mutation on the translational capacity of the cell using yeast as model system. The mutation generates a functional ribosomal protein, able to complement the translational defects of a conditional lethal mutation of yeast rpl10. However, unlike previously reported mutations, this novel RPL10 missense mutation results in an increase in the actively translating ribosome population. Our results expand the mutational and clinical spectrum of RPL10 identifying a new genetic cause of SED and highlight the emerging role of ribosomal proteins in the pathogenesis of neurodevelopmental disorders.